INTRODUCTION TO MARKETING - Shigyo Ortiz, Carlos (1998)
Many claim that we are in the Age of Marketing; they increasingly are being used in colloquial intercom everyday keywords like:. market, competition, marketing strategies, franchise, products, etc., before they have considered only the domain and use of entrepreneurs and business executives .. .